Silicon-carbon negative electrode plate based on waste graphite negative electrode material, preparation method and application

Through the eutectic solvent metallurgy process, waste graphite is converted into silicon-carbon composite materials, and high-performance silicon-carbon negative electrode sheets are prepared, solving the problem that waste lithium battery graphite cannot be effectively recycled, and achieving efficient resource utilization and environmental friendliness Improved battery performance.

CN119170920APending Publication Date: 2024-12-20DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411217452.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The graphite negative electrode materials in waste lithium batteries have not been effectively recycled and reused, resulting in waste of resources and environmental pollution, and the specific capacity of existing graphite materials is not enough to meet market demand.

Method used

The waste graphite material is converted into silicon-carbon composite material by using eutectic solvent metallurgy process, and high-performance silicon-carbon negative electrode sheets are prepared through pretreatment, extraction and ball milling for use in lithium batteries.

Benefits of technology

It improves the comprehensive utilization effect of waste resources, reduces environmental pollution, and is better than commercial graphite in terms of circulation and rate performance, provides electrochemical reactive sites in which the electrode material is fully in contact with the electrolyte, and reduces recycling costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170920A_ABST
    Figure CN119170920A_ABST
Patent Text Reader

Abstract

The invention relates to the field of recycling and application of negative electrode materials, in particular to a preparation method of a silicon-carbon negative electrode plate based on a waste graphite negative electrode material, which comprises the following steps: S1, pretreating a graphite material; s2, preparing a deep eutectic solvent; s3, regenerating the waste graphite; s4, preparing an active substance; s5, preparing a silicon-carbon negative plate; the preparation method comprises the steps of pretreatment, extraction, ball milling and the like, and the silicon-carbon negative electrode material is prepared and applied to a lithium battery. In the aspects of cycle performance and rate performance, the regenerated graphite is superior to common commercial graphite, and when the regenerated graphite is applied to a lithium battery negative electrode material, the electrode material is in full contact with an electrolyte due to the large specific surface area of the regenerated graphite, so that a large number of electrochemical reaction active sites are provided; the graphite anode material can be widely used as a new way of recycling, harmlessness and reduction of the graphite anode material after a hydrometallurgy process; the extraction agent is green, low in toxicity and environment-friendly, so that the cost of recovering graphite after the hydrometallurgy process is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of negative electrode material recovery and application, and in particular to a silicon-carbon negative electrode sheet based on waste graphite negative electrode material, a preparation method and application thereof. Background Art

[0002] With the widespread use of electric vehicles and electronic devices, the number of waste lithium batteries is also increasing rapidly. 12-21% of the composition of waste lithium batteries is graphite, and the cost accounts for about 15% of the entire lithium-ion battery. It is predicted that the demand for battery-grade graphite will reach 285 million tons in 2035. However, natural graphite has problems such as long formation cycle and high cost of artificial graphite. Therefore, the regeneration of waste lithium battery negative electrode graphite can alleviate the pressure on the negative electrode material supply chain and meet the growing demand for battery-grade graphite. At present, people mainly use wet recycling processes to recover relatively high-value metal elements such as lithium and cobalt, and most of the graphite negative electrode materials are abandoned as solid waste. These graphite materials contain 68 types of impurity elements, including heavy metals copper and nickel, plant nutrient elements phosphorus, etc. If not handled properly, it will inevitably lead to environmental problems such as waste of resources, eutrophication of water bodies and excessive heavy metals in soil.

[0003] A low eutectic solvent is a two-component or three-component low eutectic mixture composed of a certain stoichiometric ratio of hydrogen bond acceptors and hydrogen bond donors. Its characteristic is that its freezing point is significantly lower than the melting point of each component pure substance, and it is green, low-toxic and environmentally friendly. At present, the theoretical specific capacity of graphite negative electrode materials is only 372mAh·g -1 , which is not enough for the market demand. Silicon-carbon composite material is a high-energy composite material with a theoretical specific capacity of 4200mAh·g -1 . Column 2 of the "Guiding Opinions on Promoting the Development of the Energy Electronics Industry" (MIIT Joint Electronics

[2022] No. 181) is "Action to Improve the Supply Capacity of New Energy Storage Battery Products and Technologies", which proposes to support the development of ultra-long life and high-safety performance lithium-ion batteries, optimize the design and manufacturing process, and improve the safety and economy of the battery throughout its life cycle from multiple dimensions such as materials, units, and systems. Therefore, under the background of dual carbon, the present invention discloses an invention of green recycling of waste lithium battery negative electrode graphite materials after hydrometallurgical process and preparing it into a new silicon-carbon composite material, which is then applied to new energy devices. Summary of the invention

[0004] Based on this, the purpose of the present invention is to provide a silicon-carbon negative electrode sheet based on waste graphite negative electrode material, a preparation method and application, which can improve the comprehensive utilization of waste resources, reduce pollution to the environment, and have important social and economic benefits.

[0005] The present invention adopts the following technical solution:

[0006] A method for preparing a silicon-carbon negative electrode sheet based on waste graphite negative electrode material comprises the following steps:

[0007] S1. Pretreatment of graphite material: Place the waste graphite material after the hydrometallurgical process in an oven to dry, take it out and grind it into powder, recorded as SG;

[0008] S2. Prepare a low eutectic solvent: accurately weigh the corresponding mass of choline chloride and oxalic acid in a beaker according to a certain molar ratio, heat and stir at 80°C-100°C until a transparent and uniform DES system is formed, cool to room temperature and store, and record it as DES-1;

[0009] S3, regenerated waste graphite: (1) 0.1g-0.6g of SG and 12mL of DES-1 were mixed and transferred to a reactor for reaction. After the reaction was completed, the graphite powder was centrifuged and washed with ultrapure water, which was recorded as SG-D; (2) The SG-D was placed in a muffle furnace for heating treatment, and after cooling to room temperature, regenerated graphite was obtained, which was recorded as RC;

[0010] S4. Preparation of active substances: accurately weighing a certain mass ratio of regenerated graphite, nano-silicon and glucose in a ball milling jar, and placing them in a ball mill to obtain active substances, which are recorded as Si / C;

[0011] S5. Preparation of silicon-carbon negative electrode sheet: accurately weigh a certain mass ratio of active material, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber in a ball mill, and place it in a ball mill for ball milling. After the slurry is uniform, use an automatic coater to evenly coat the slurry on the rough surface of a single-sided copper foil. The coated product is placed in a vacuum drying oven for vacuum drying to obtain a silicon-carbon negative electrode sheet; the larger silicon-carbon negative electrode sheet is rolled and cut into smaller electrodes with a slicer for loading into button batteries.

[0012] A further improvement to the above technical solution is that in step S1, the drying temperature is 100°C-200°C, and the drying time is 12h-72h.

[0013] A further improvement to the above technical solution is that in step S2, the molar ratio of choline chloride to oxalic acid is 1:1-2.

[0014] A further improvement to the above technical solution is that in step S3, when the reactor is reacting, the reaction temperature is 100°C-120°C, and the reaction time is 40min-90min; when heating in the muffle furnace, the heating temperature is 300°C-350°C, and the insulation time is 3h-12h.

[0015] A further improvement to the above technical solution is that in step S4, the mass ratio of regenerated graphite, nano-silicon and glucose is 27-31:4-8:5.

[0016] A further improvement to the above technical solution is that in step S4, the rotation speed of the ball mill is 400 r / min-800 r / min, and the ball milling time is 10 h-20 h.

[0017] A further improvement to the above technical solution is that in step S5, the rotation speed of the ball mill is 200 r / min-600 r / min.

[0018] A silicon-carbon negative electrode sheet based on waste graphite negative electrode material is prepared by using the above-mentioned preparation method.

[0019] An application of a silicon-carbon negative electrode sheet based on waste graphite negative electrode material, using the above-mentioned silicon-carbon negative electrode sheet, the silicon-carbon negative electrode sheet is applied to a lithium battery.

[0020] A further improvement to the above technical solution is that the assembly method of the lithium battery includes the following steps: in a glove box, firstly, a silicon-carbon negative electrode sheet is placed in the middle of a positive electrode shell, then an appropriate amount of electrolyte is dripped into the silicon-carbon negative electrode sheet to soak the silicon-carbon negative electrode sheet, and then a diaphragm is completely covered on the silicon-carbon negative electrode sheet, and an appropriate amount of electrolyte is dripped into the diaphragm again to soak the diaphragm, and then a lithium sheet, a gasket, a spring sheet, and a negative electrode shell are added in sequence, and a CR2032 button-type lithium battery is obtained after pressing; after the lithium battery is left to stand for 12 hours, it is placed in a LANDCT3001A system to start a cycle performance test and a rate performance test.

[0021] The beneficial effects of the present invention are:

[0022] The present invention prepares silicon-carbon negative electrode materials through pretreatment, extraction, ball milling and other methods, and applies them to lithium batteries. In terms of cycle performance and rate performance, the regenerated graphite of the present invention is superior to ordinary commercial graphite. Moreover, when the regenerated graphite is applied to the negative electrode material of lithium batteries, its large specific surface area enables the electrode material to fully contact with the electrolyte, providing a large number of electrochemical reaction active sites, and can be widely used as a new way to recycle, detoxify and reduce the amount of graphite negative electrode materials after hydrometallurgical processes. The extractant in the present invention is green, low-toxic and environmentally friendly, thereby reducing the cost of recovering graphite after hydrometallurgical processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 : are Raman spectra of the regenerated graphite (RC) and commercial graphite (CC) in Example 1 of the present invention;

[0024] Figure 2 is the SEM image of the regenerated graphite (RC) in Example 1;

[0025] Figure 3 is the SEM image of commercial graphite (CC) in Example 1;

[0026] Figure 4 is the C fine spectrum of the regenerated graphite (RC) XPS in Example 1;

[0027] Figure 5 is the N fine spectrum of the regenerated graphite (RC) XPS in Example 1;

[0028] Figure 6 is the O fine spectrum of the regenerated graphite (RC) XPS in Example 1;

[0029] Figure 7 is the P fine spectrum of the regenerated graphite (RC) XPS in Example 1;

[0030] Figure 8 is the S fine spectrum of the regenerated graphite (RC) XPS in Example 1;

[0031] Fig. 9 The RC electrode and CC electrode in Example 1 are at a current density of 100 mA g -1 Cycle performance diagram of

[0032] Fig.10 The RC and CC electrodes in Example 1 are at 0.2 A·g -1 To 3A·g -1 The rate performance diagram;

[0033] Fig.11 The Si8% electrode in Example 2 is charged at a current density of 100 mA·g -1 Cycle performance diagram of

[0034] Fig.12 The Si12% electrode in Example 3 is charged at a current density of 100 mA·g -1 Cycle performance diagram of

[0035] Fig.13 The Si16% electrode in Example 4 is charged at a current density of 100 mA·g -1 Cycle performance diagram. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In the description of the present invention, it should be noted that the terms "vertical direction", "up", "down", "horizontal", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, "first", "second", "third", and "fourth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0038] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection, it can be a mechanical connection, it can be an electrical connection, it can be a direct connection, it can be connected through an intermediate medium, and it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0039] Example 1

[0040] The preparation method and application of the silicon-carbon negative electrode sheet based on waste graphite negative electrode material provided in this embodiment include the following steps:

[0041] S1. Pretreatment of graphite material: Place the waste graphite material after the hydrometallurgical process in an oven and dry it for 24 hours, then take it out and grind it into powder, which is recorded as SG;

[0042] S2. Prepare a deep eutectic solvent (DES): according to the molar ratio of choline chloride to oxalic acid of 1:1, accurately weigh the corresponding mass of reagents in a beaker, heat and stir at 80°C until a transparent and uniform DES system is formed, cool to room temperature and store, and record it as DES-1;

[0043] S3, regenerated waste graphite: (1) 0.1 g of SG and 12 mL of DES-1 were mixed and transferred to a reactor for reaction at a temperature of 120°C and a reaction time of 60 min. After the reaction was completed, the graphite powder was centrifuged and washed with ultrapure water and recorded as SG-D; (2) The SG-D was placed in a muffle furnace for heating at a temperature of 300°C and a holding time of 10 h. After cooling to room temperature, regenerated graphite was obtained and recorded as RC;

[0044] S4. Preparation of silicon-carbon negative electrode sheet: Accurately weigh the corresponding mass of reagents in a ball mill according to the mass ratio of regenerated graphite: conductive carbon black: sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 40:5:3:2, and place them in a ball mill for ball milling. After the slurry is uniform, use an automatic coating machine to evenly coat the slurry on the rough surface of a single-sided copper foil. The coated product is placed in a vacuum drying oven for vacuum drying to obtain a silicon-carbon negative electrode sheet. The larger silicon-carbon negative electrode sheet is rolled and cut into smaller pieces with a slicer for loading into button batteries;

[0045] S5. Battery assembly and testing:

[0046] In the glove box, first place the silicon-carbon negative electrode sheet in the middle of the positive electrode shell, then drip an appropriate amount of electrolyte to soak the silicon-carbon negative electrode sheet, and then completely cover the diaphragm on the silicon-carbon negative electrode sheet, drip an appropriate amount of electrolyte again to soak the diaphragm, and then add lithium sheets, gaskets, springs, and negative electrode shells in turn, and after pressing, the CR2032 button lithium battery is obtained.

[0047] After the lithium battery was left to rest for 12 hours, it was placed in the LAND CT3001A system to begin cycle performance testing and rate performance testing.

[0048] Example 2

[0049] The preparation method and application of the silicon-carbon negative electrode sheet based on waste graphite negative electrode material provided in this embodiment include the following steps:

[0050] S1. Pretreatment of graphite material: Place the waste graphite material after the hydrometallurgical process in an oven and dry it for 24 hours, then take it out and grind it into powder, which is recorded as SG;

[0051] S2. Prepare a deep eutectic solvent (DES): according to the molar ratio of choline chloride to oxalic acid of 1:1, accurately weigh the corresponding mass of reagents in a beaker, heat and stir at 80°C until a transparent and uniform DES system is formed, cool to room temperature and store, and record it as DES-1;

[0052] S3, regeneration of waste graphite: (1) after mixing 0.1 g of SG and 12 mL of DES-1, transfer to a reactor for reaction at a reaction temperature of 120°C and a reaction time of 60 min. after the reaction is completed, centrifuge and wash the reacted graphite powder with ultrapure water, which is recorded as SG-D; (2) place the SG-D in a muffle furnace for heating treatment, the heating temperature is controlled at 300°C, the insulation time is controlled at 10 h, and after cooling to room temperature, regenerated graphite is obtained, which is recorded as RC;

[0053] S4. Preparation of active substances: According to the mass ratio of regenerated graphite: nano-silicon: glucose = 31:4:5, the corresponding mass of reagents are accurately weighed in a ball milling jar, and the jar is placed in a ball mill and circulated at a progressive speed of 400 r / min, 600 r / min and 800 r / min for 20 hours to obtain active substances, which are recorded as Si8%;

[0054] S5. Preparation of silicon-carbon negative electrode sheet: accurately weigh the corresponding mass of reagents in a ball mill according to the mass ratio of regenerated graphite: conductive carbon black: sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 40:5:3:2, and place the mixture in a ball mill, and after the slurry is uniform, use an automatic coating machine to evenly coat the slurry on the rough surface of a single-sided copper foil, and place the coated product in a vacuum drying oven for vacuum drying to obtain a silicon-carbon negative electrode sheet; roll the obtained silicon-carbon negative electrode sheet with a larger size, and then use a slicer to cut out smaller electrode sheets so as to be loaded into button batteries;

[0055] S6. Battery assembly and testing: In the glove box, first place the silicon-carbon negative electrode sheet in the middle of the positive electrode shell, then drip an appropriate amount of electrolyte to soak the silicon-carbon negative electrode sheet, and then completely cover the diaphragm on the silicon-carbon negative electrode sheet, drip an appropriate amount of electrolyte again to soak the diaphragm, and then add lithium sheets, gaskets, springs, and negative electrode shells in turn, and press them to obtain a CR2032 button lithium battery;

[0056] After the lithium battery was left to rest for 12 hours, it was placed in the LAND CT3001A system to begin cycle performance testing and rate performance testing.

[0057] Example 3

[0058] The preparation method and application of the silicon-carbon negative electrode sheet based on waste graphite negative electrode material provided in this embodiment include the following steps:

[0059] S1. Pretreatment of graphite material: Place the waste graphite material after the hydrometallurgical process in an oven and dry it for 24 hours, then take it out and grind it into powder, which is recorded as SG;

[0060] S2. Prepare a low eutectic solvent: according to the molar ratio of choline chloride to oxalic acid of 1:1, accurately weigh the corresponding mass of reagents in a beaker, heat and stir at 80°C until a transparent and uniform DES system is formed, cool to room temperature and store, and record it as DES-1;

[0061] S3, regenerated waste graphite: (1) 0.1 g of SG and 12 mL of DES-1 were mixed and transferred to a reactor for reaction at a temperature of 120°C and a reaction time of 60 min. After the reaction was completed, the graphite powder was centrifuged and washed with ultrapure water and recorded as SG-D; (2) The SG-D was placed in a muffle furnace for heating at a temperature of 300°C and a holding time of 10 h. After cooling to room temperature, regenerated graphite was obtained and recorded as RC;

[0062] S4. Preparation of active substances: accurately weigh the corresponding mass of reagents in a ball mill according to the mass ratio of regenerated graphite: nano-silicon: glucose = 29:6:5, and place them in a ball mill for 20 hours at a progressive speed of 400 r / min, 600 r / min and 800 r / min to obtain active substances, which are recorded as Si 12%;

[0063] S5: Preparation of silicon-carbon negative electrode sheet: Accurately weigh the corresponding mass of reagents in a ball mill according to the mass ratio of regenerated graphite: conductive carbon black: sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 40:5:3:2, and place them in a ball mill for ball milling. After the slurry is uniform, use an automatic coating machine to evenly coat the slurry on the rough surface of a single-sided copper foil. The coated product is placed in a vacuum drying oven for vacuum drying to obtain a silicon-carbon negative electrode sheet; the obtained larger silicon-carbon negative electrode sheet is rolled and then cut into smaller electrode sheets using a slicer for loading into button batteries;

[0064] S6. Battery assembly and testing: In the glove box, first place the silicon-carbon negative electrode sheet in the middle of the positive electrode shell, then drip an appropriate amount of electrolyte to soak the silicon-carbon negative electrode sheet, and then completely cover the diaphragm on the silicon-carbon negative electrode sheet, drip an appropriate amount of electrolyte again to soak the diaphragm, and then add lithium sheets, gaskets, springs, and negative electrode shells in turn, and press them to obtain a CR2032 button lithium battery;

[0065] After the lithium battery was left to rest for 12 hours, it was placed in the LAND CT3001A system to begin cycle performance testing and rate performance testing.

[0066] Example 4

[0067] The preparation method and application of the silicon-carbon negative electrode sheet based on waste graphite negative electrode material provided in this embodiment include the following steps:

[0068] S1. Pretreatment of graphite material: Place the waste graphite material after the hydrometallurgical process in an oven and dry it for 24 hours, then take it out and grind it into powder, which is recorded as SG;

[0069] S2. Prepare a low eutectic solvent: according to the molar ratio of choline chloride to oxalic acid of 1:1, accurately weigh the corresponding mass of reagents in a beaker, heat and stir at 80°C until a transparent and uniform DES system is formed, cool to room temperature and store, and record it as DES-1;

[0070] S3, regenerated waste graphite: (1) 0.1 g of SG and 12 mL of DES-1 were mixed and transferred to a reactor for reaction at a temperature of 120°C and a reaction time of 60 min. After the reaction was completed, the graphite powder was centrifuged and washed with ultrapure water and recorded as SG-D; (2) The SG-D was placed in a muffle furnace for heating at a temperature of 300°C and a holding time of 10 h. After cooling to room temperature, regenerated graphite was obtained and recorded as RC;

[0071] S4. Preparation of active substances: accurately weigh the corresponding mass of reagents in a ball mill according to the mass ratio of regenerated graphite: nano-silicon: glucose = 27:8:5, and place them in a ball mill for 20 hours at a progressive speed of 400 r / min, 600 r / min and 800 r / min to obtain active substances, which are recorded as Si 16%;

[0072] S5. Preparation of silicon-carbon negative electrode sheet: Accurately weigh the corresponding mass of reagents in a ball mill according to the mass ratio of regenerated graphite: conductive carbon black: sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 40:5:3:2, and place them in a ball mill. After the slurry is uniform, use an automatic coating machine to evenly coat the slurry on the rough surface of a single-sided copper foil. The coated product is placed in a vacuum drying oven for vacuum drying to obtain a silicon-carbon negative electrode sheet. The larger silicon-carbon negative electrode sheet is rolled and cut into smaller pieces with a slicer for loading into button batteries;

[0073] S6. Battery assembly and testing: In the glove box, first place the silicon-carbon negative electrode sheet in the middle of the positive electrode shell, then drip an appropriate amount of electrolyte to soak the silicon-carbon negative electrode sheet, and then completely cover the diaphragm on the silicon-carbon negative electrode sheet, drip an appropriate amount of electrolyte again to soak the diaphragm, and then add lithium sheets, gaskets, springs, and negative electrode shells in turn, and press them to obtain a CR2032 button lithium battery;

[0074] After the lithium battery was left to rest for 12 hours, it was placed in the LAND CT3001A system to begin cycle performance testing and rate performance testing.

[0075] The regenerated graphite (RC) material in Example 1 was characterized by Raman, SEM and XPS.

[0076] Please refer to 1. Both recycled graphite (RC) and commercial graphite (CC) have the D peak and G peak of carbon materials, where the upper curve is recycled graphite (RC) and the lower curve is commercial graphite (CC).

[0077] Please refer to 2. The surface of regenerated graphite (RC) presents a fine flake structure, which is evenly distributed on the surface, increasing the contact between the electrode material and the electrolyte and providing more active sites for electrochemical reactions.

[0078] Refer to 9, at a current density of 100 mA g -1 Under all conditions, the discharge specific capacity of the RC electrode is higher than that of the CC electrode, so the cycle performance of the recycled graphite (RC) is better than that of the commercial graphite (CC).

[0079] See 10. The RC electrode exhibits excellent rate performance at current densities of 0.2 A g -1 , 0.5A·g -1 , 1A·g -1 , 2A·g -1 and 3A·g -1 The reversible discharge capacity is 430.1 mAh g -1 、346.6mAh·g -1 、280.7mAh·g -1 、175.4mAh·g -1 、133.6mAh·g -1 , and when the current density increases from 3A·g -1 Back to 0.2A·g -1 When the discharge capacity is increased, it returns to the initial level. From the rate performance test, it is found that the rate performance of recycled graphite (RC) is better than that of commercial graphite (CC).

[0080] from Fig.11 It can be seen that at a current density of 100 mA g -1 Under the condition of 122 cycles, the discharge capacity of Si8% electrode is 821.3 mAh g -1 , the capacity retention rate is 72.89%.

[0081] from Fig.12 It can be seen that at a current density of 100 mA g -1 Under the condition of 12% Si electrode, the discharge capacity after 100 cycles is 1253.7 mAh g -1 , the capacity retention rate is 76.62%.

[0082] from Fig.13 It can be seen that at a current density of 100 mA g -1 Under the condition of 16% Si electrode, the discharge capacity after 100 cycles is 1506.1 mAh g -1 , the capacity retention rate is 72.91%.

[0083] Compared with the prior art, the present invention prepares silicon-carbon negative electrode materials through pretreatment, extraction and ball milling, and applies them to lithium batteries; in terms of cycle performance and rate performance, the regenerated graphite of the present invention is superior to ordinary commercial graphite, and when the regenerated graphite is applied to lithium battery negative electrode materials, its large specific surface area enables the electrode material to fully contact with the electrolyte, providing a large number of electrochemical reaction active sites, and can be widely used as a new way to resource, harmlessly and reduce the amount of graphite negative electrode materials after hydrometallurgical process; the extractant in the present invention is green, low-toxic and environmentally friendly, thereby reducing the cost of recovering graphite after hydrometallurgical process.

[0084] The above only expresses the preferred technical solution of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A method for preparing a silicon-carbon negative electrode sheet based on waste graphite negative electrode material, characterized in that: The steps include: S1. Pretreatment of graphite material: Place the waste graphite material after the hydrometallurgical process in an oven to dry, take it out and grind it into powder, recorded as SG; S2. Prepare a low eutectic solvent: accurately weigh the corresponding mass of choline chloride and oxalic acid in a beaker according to a certain molar ratio, heat and stir at 80°C-100°C until a transparent and uniform DES system is formed, cool to room temperature and store, and record it as DES-1; S3, regenerated waste graphite: (1) 0.1g-0.6g of SG and 12mL of DES-1 were mixed and transferred to a reactor for reaction. After the reaction was completed, the graphite powder was centrifuged and washed with ultrapure water, which was recorded as SG-D; (2) The SG-D was placed in a muffle furnace for heating treatment, and after cooling to room temperature, regenerated graphite was obtained, which was recorded as RC; S4. Preparation of active substances: accurately weigh a certain mass ratio of regenerated graphite, nano-silicon and glucose in a ball milling jar, and place them in a ball mill to obtain active substances, which are recorded as Si / C; S5. Preparation of silicon-carbon negative electrode sheet: accurately weigh a certain mass ratio of active material, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber in a ball mill, and place it in a ball mill for ball milling. After the slurry is uniform, use an automatic coater to evenly coat the slurry on the rough surface of a single-sided copper foil. The coated product is placed in a vacuum drying oven for vacuum drying to obtain a silicon-carbon negative electrode sheet; the larger silicon-carbon negative electrode sheet is rolled and cut into smaller electrodes with a slicer for loading into button batteries.

2. The method for preparing a silicon-carbon negative electrode sheet based on waste graphite negative electrode material according to claim 1, characterized in that: In step S1, the drying temperature is 100°C-200°C, and the drying time is 12h-72h.

3. The method for preparing a silicon-carbon negative electrode sheet based on waste graphite negative electrode material according to claim 1, characterized in that: In step S2, the molar ratio of choline chloride to oxalic acid is 1:1-2.

4. The method for preparing a silicon-carbon negative electrode sheet based on waste graphite negative electrode material according to claim 1, characterized in that: In step S3, when the reactor is reacting, the reaction temperature is 100°C-120°C, and the reaction time is 40min-90min; when the muffle furnace is heated, the heating temperature is 300°C-350°C, and the insulation time is 3h-12h.

5. The method for preparing a silicon-carbon negative electrode sheet based on waste graphite negative electrode material according to claim 1, characterized in that: In step S4, the mass ratio of regenerated graphite, nano-silicon and glucose is 27-31:4-8:

5.

6. The method for preparing a silicon-carbon negative electrode sheet based on waste graphite negative electrode material according to claim 1, characterized in that: In step S4, the ball milling speed is 400 r / min-800 r / min, and the ball milling time is 10 h-20 h.

7. The method for preparing a silicon-carbon negative electrode sheet based on waste graphite negative electrode material according to claim 1, characterized in that: In step S5, the rotation speed of the ball mill is 200 r / min-600 r / min.

8. A silicon-carbon negative electrode sheet based on waste graphite negative electrode material, characterized in that: The silicon-carbon negative electrode sheet based on waste graphite negative electrode material is prepared using the preparation method described in any one of claims 1 to 7.

9. An application of a silicon-carbon negative electrode sheet based on waste graphite negative electrode material, characterized in that: The silicon-carbon negative electrode sheet as claimed in claim 8 is used in a lithium battery.

10. The use of the silicon-carbon negative electrode sheet based on waste graphite negative electrode material according to claim 9, characterized in that: The lithium battery assembly method comprises the following steps: firstly placing a silicon-carbon negative electrode sheet in the middle of a positive electrode shell in a glove box, then dripping an appropriate amount of electrolyte to soak the silicon-carbon negative electrode sheet and then completely covering the diaphragm on the silicon-carbon negative electrode sheet, dripping an appropriate amount of electrolyte again to soak the diaphragm, then sequentially adding a lithium sheet, a gasket, a spring sheet, and a negative electrode shell, and pressing the sheets to obtain a CR2032 button-type lithium battery; after the lithium battery is left to stand for 12 hours, it is placed in a LAND CT3001A system to start a cycle performance test and a rate performance test.